Articulate Storyline 3 Interactive Media to Increase Learning Interest and Activeness of Fifth Grade Elementary School Students - Aida Fauziah Majid; Sekar Purbarini Kawuryana (Universitas Pendidikan Ganesha, 2023)
Learning material in grade V elementary school begins to cover abstract matters. Students' level of interest in learning and activeness still needs to be higher. This research aims to create interactive media to articulate storyline 3 that is feasible and effective. The type of research used is research and development (RnD), based on the model developed by Borg and Gall with ten stages. The research subjects involved 105 grade V elementary school students. Data collection methods include interviews, observations and questionnaires. Interactive media is tested through initial, expanded, and operational trials. The effectiveness of interactive media was analyzed using a quasi-experiment in the experimental and control classes. The research results show that the validation test scores for interactive media products based on material experts are in the very feasible category, and the validation scores by media experts are in the very feasible category. The research results showed that there were significant differences in interactive media between the experimental class and the control class. Based on the data obtained, the interactive media Articulate Storyline 3 meets the appropriate and effective criteria for fifth-grade elementary school learning. The implications of this research can be used as a reference for teachers in choosing applications that can be used in developing interactive media.